ANALISIS FLEXIBLE WORK ARRANGEMENTS PADA PT XYZ - Utami Nurwati; Christian Wiradendi Wolor; Eka Dewi Utari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Flexible Work Arrangements (FWA) is a policy that provides flexibility to employees, this flexibility can be in the form of work time or location. This research aims to understand the implementation of Flexible Work Arrangements (FWA) at PT XYZ and its effect on work productivity and efficiency. The method used in this research is a qualitative case study with data collection techniques through interviews, observation, and documentation, and data analysis using the Miles and Huberman interactive model. The results showed that PT XYZ implements FWA with a hybrid work policy system, flexitime, and working to change locations according to work needs which are considered to have a positive impact on productivity and operational efficiency. However, in its implementation there are still challenges in terms of coordination, work supervision, and work schedule arrangements. Therefore, it is necessary to optimize communication and monitoring so that the implementation of Flexible Work Arrangements (FWA) can run more effectively.